Biodiversity Patterns of Rocky Coastal and Human-Made Structures in Gheshm Shorelines; Role of Slope and Tidal Levels Characteristics in Determining Patterns of Biodiversity - Marzieh Razaghi; Ali Nasrolahi; Ehsan Kamrani; Mohammad Sharif Ranjbar; Amir Vazirizadeh (محیط زیست و توسعه فرابخشی)
Introduction: The coastal landscapes are constantly changing due to the increasing demand for structures aimed at economic, residential, and tourism activities. Human-made constructions such as breakwaters, piers, and seawalls have become characteristic features alongside shallow habitats in intertidal and subtidal zones. This transformation accelerates in response to exponential population growth and climate change impacts, such as rising sea levels and the need to mitigate natural disasters like storm surges. Concerns about the ecological value of these created environments have sparked efforts to establish new habitats to enhance biodiversity. Therefore, this study aimed to compare biodiversity patterns between artificial and natural substrates, as well as to investigate the role of slope and tidal height characteristics in determining biodiversity patterns.Materials and Methods: Sampling was conducted in four natural habitats (rocky shores of Naz Island, Mosen, Naqashah, and Ramchah) and four artificial habitats (rocky substrates of Naz Island breakwaters, fish processing waste, Selakh, and Ramchah) along the southern shores of Qeshm Island, seasonally from summer 2016 to spring 2017. During this study, 960 photographs were taken of epibiotic communities from two types of substrates across eight stations and three tidal levels over four sampling periods.Results: After analyzing the photographs and identifying the collected samples, 105 species were identified, of which 65 species were found in natural substrates and 42 species in artificial substrates. Natural substrates exhibited a higher abundance (percentage cover) of epibiotic communities compared to artificial ones. Most taxonomic groups identified had higher percentage cover in natural substrates, except for three groups: hydroids, bryozoans, and sponge-like organisms, which were more abundant in artificial substrates. A similar trend was observed in the number of species, with the stations of Mosen, Ramchah, and Naqashah hosting the highest species counts. The results indicated greater species diversity in natural substrates (14.99) compared to artificial ones (9.98). PERMANOVA tests revealed significant differences in the structure of epibiotic communities between natural and artificial hard substrates, as well as across different tidal levels on the southern shores of Qeshm Island (p < 0.05).Discussion: A nearly regular increasing trend in species count was observed with rising tidal height, with lower intertidal areas hosting higher species richness compared to the other two tidal levels. No echinoderm individuals were found on the flat surfaces of artificial habitats, likely due to the steep slope and lack of microhabitats, which prevented these communities from establishing. In examining the cleaner species in both natural and artificial habitats, it was found that the distribution and growth of the algae Padina sp. on artificial substrates had significantly decreased compared to natural ones. This macroalga was one of the key species influencing the population structure differences between the two habitats. The steep slopes and high wave energy in artificial substrates likely hindered the successful spread of this species. In contrast, the macroalga Centroceras clavulatum successfully adapted to artificial structures and established significant coverage on these substrates, making it one of the key species influencing the differences in population structure between the two habitats, following Padina sp. This study demonstrated that creating low-slope surfaces leads to a broader range of habitats, increasing substrate heterogeneity and thereby providing multiple ecological niches for various species, ultimately enhancing regional biodiversity.